Analysis of the AISAS Model in the Digital Marketing Strategy of Our Bento in Tasikmalaya City - Balebat Dwi Adisubagja; Adam Hermawan; Btari Mariska Purwaamijaya (International Journal of Economics Development Research (IJEDR), 2024)
The Food and Beverage industry is currently experiencing rapid growth, and every sector within it must innovate to maintain a competitive edge. This study discusses sales in culinary products analyzed through the AISAS model (Attention, Interest, Search, Action, Share). The research subjects are informants who are the owners of Our Bento. Our Bento is an SME in the culinary field that combines modern and traditional flavors. This descriptive research gathers data through interviews. The results of the AISAS model analysis in digital marketing strategy include: 1. Attention (consumer attention through visual content), 2. Interest (consumers receive information, generate interest, and feel compelled to seek more information), 3. Search (consumers have a high level of curiosity), 4. Action (consumers decide to use the offered products), 5. Share (satisfied consumers are likely to share with others).